(untitled) (Fiep Bulletin - online, 2015)
The analysis of the results obtained has shown that the ability to jump is more strongly connected with age that with rapidity. In the period from 8 to 18 years of age this ability, as a feature of efficiency, increases in a systematic way, the average amounting to 3,39 cm in the group of chronological age and to 2,32 in the group of physiological age.